Economic Impact of India's Family Planning Programme on School Age Population During 1971-1991 - International Institute for Population Studies (International Institute for Population Studies, 1972)
O.P. Vig’s study on the economic impact of India’s Family Planning Programme between 1971 and 1991 presents a detailed demographic and fiscal analysis of how population control measures influenced the school-age population and educational expenditure. The research highlights compulsory education policies and demographic growth as the primary forces shaping school enrollment trends, while emphasizing the role of fertility decline driven by the national family planning initiative launched in 1962. By employing population projections based on age-specific fertility and mortality rates, and assuming negligible migration, the study estimates that approximately 131.96 million potential school enrollments were averted over the two decades due to reduced birth rates. The analysis further evaluates per capita educational expenditure across primary, upper primary, and secondary levels, projecting substantial fiscal savings ranging from Rs. 3,198 to Rs. 4,205 million annually by 1991. These savings significantly exceed the operational costs of the family planning programme, demonstrating its long-term economic benefits. Additionally, the study forecasts a 30–44 percent reduction in enrollment across educational levels by 1991 under effective implementation scenarios. Overall, the findings underscore the strong interconnection between population policy and educational planning, suggesting that sustained fertility reduction not only moderates demographic pressures but also enhances the efficiency of educational investments, thereby supporting broader socioeconomic development objectives in India.
International Institute for Population Studies Deonar, Bombay-400088
Keywords: India’s Family Planning Programme; School-Age Population; Compulsory Education; Birth Rate Decline; Population Projections; Educational Expenditure; Demographic Transition; Fertility Rates; Enrollment Reduction; Economic Savings; Fifth Five Year Plan; Education Infrastructure Planning